The “Szymanowski Clash”: Harmonic Conflict and Ambiguity in the Szymanowski Mazurkas - Bengtson, Matthew (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2016)
Among the greatest fascinations of Karol Szymanowski’s Mazurkas, op. 50 and op. 62, are their rich and sophisticated harmonic vocabulary. Many stylistic elements are combined together in this musical language, including pedal points, bagpipe fifths, modal mixture, and bitonality. The interplay of all these phenomena tends to destabilize functional harmonic relationships, leading to many instances of harmonic clashes by semitone, dubbed “Szymanowski clashes.” Considering this harmonic language through the lens of the Szymanowski clash can offer an understanding of this music that points to underlying compositional design and structural logic, while acting in accord with the listener’s perceptions of the musical surface.